ANALISIS PERJANJIAN PERKAWINAN SEBAGAI PERLINDUNGAN HAK PEREMPUAN DALAM ADAT BATAK TOBA DITINJAU DARI HUKUM PERKAWINAN - NIM. A1012201011, DESPRY YOLANDA (Jurnal Fatwa Hukum, 2024)
Abstrac  An agreement is something that can touch various aspects of life, including the aspect of marriage. Marriage is a legal act that has legal consequences, namely the unity of assets obtained during the marriage. This provision of property union can be circumvented by making a marriage agreement.Regulations regarding marriage agreements can be seen in Law Number 1 of 1974 Article 29 and in the Civil Code Book I Chapter VII Articles 139 to Article 154. Marriage agreements are usually made if someone who wants to marry has valuable assets or hopes will gain wealth. By entering into a marriage agreement, there is legal certainty regarding what has been agreed.These regulations have the same aim, namely to regulate the consequences of marriage on assets that deviate from the unity of assets. However, in Batak traditional marriages, marriage agreements are still considered taboo and are considered not in accordance with the purpose of marriage in Batak tradition. This is where the author is interested in examining the comparison of pre-nuptial agreements regarding assets between Law Number 1 of 1974 and the Civil Code.This research aims to analyze marriage agreements as a means of protecting women's rights in Toba Batak traditional marriages, and also to analyze the legal consequences of marriage agreements in Toba Batak traditional marriages in terms of positive law. Marriage agreements in the Toba Batak tradition are still very taboo for couples who are going to get married or are already married, this is because the marriage agreement is not in accordance with the purpose of marriage according to the Toba Batak tradition. This research is a normative juridical research method.Marriage agreements in the Toba Batak tradition are still considered taboo, but marriage agreements can be a way out of problems regarding women's rights in Batak traditional marriages. In Batak Toba customs, marriage agreements are strictly prohibited and if it is discovered that the couple has made a marriage agreement, it will most likely be canceled and sanctions will also be imposed.Key words: marriage agreement, Batak Toba customs, women's rights.  Abstrak  Perjanjian merupakan hal yang dapat menyentuh berbagai aspek kehidupan tanpa terkecuali dalam aspek perkawinan. perkawinan merupakan perbuatan hukum yang mempunyai akibat hukum yaitu persatuan harta yang didapat selama perkawinan berlangsung. Ketentuan persatuan harta ini dapat disimpangi dengan membuat perjanjian perkawinan.Pengaturan tentang perjanjian perkawinan dapat dilihat dalam Undang-Undang Nomor 1 Tahun 1974 Pasal 29 dan dalam Kitab Undang-Undang Hukum Perdata Buku I Bab VII Pasal 139 sampai dengan Pasal 154. Perjanjian perkawinan biasanya dibuat jika seseorang yang hendak menikah mempunyai harta yang berharga atau mengharapkan akan memperoleh kekayaan. Dengan diadakannya perjanjian perkawinan, terdapat kepastian hukum terhadap apa yang diperjanjikan.Peraturan-peraturan tersebut memiliki tujuan yang sama yaitu untuk mengatur akibat perkawinan terhadap harta kekayaan yang menyimpangi dari persatuan harta. Namun dalam perkawinan adat batak perjanjian perkawinan masih dianggap tabu dan dan dianggap tidak sesuai dengan tujuan perkawinan dalam adat batak. Di sinilah penulis tertarik untuk meneliti perbandingan perjanjian pra nikah mengenai harta kekayaan antara Undang-Undang Nomor 1 Tahun 1974 dengan Kitab Undang-Undang Hukum Perdata.Penelitian ini bertujuan untuk menganalisis perjanjian perkawinan sebagai sarana perlindungan hak Perempuan dalam perkawinan adat Batak Toba, dan juga untuk menganalisis akibat hukum perjanjian perkawinan dalam perkawinan adat Batak Toba Ditinjau Dari Hukum Positif. Perjanjian Perkawinan dalam adat Batak Toba masih sangat tabu untuk dilakukan oleh pasangan baik yang akan maupun sudah menikah, hal ini dikarenakan perjanjian perkawinan tidak sesuai dengan tujuan perkawinan menurut adat Batak Toba. Penelitian ini adalah penelitian metode penelitian yuridis normatif.Perjanjian perkawinan dalam adat Batak Toba masih dianggap tabu, namun perjanjian perkawinan dapat menjadi jalan keluar dari permasalahan mengenai hak Perempuan dalam pekawinan adat batak. dalam adata batak toba perjanjian perkawinan sangatlah dilarang dan jika ketahuan pasangan tersebut membuat perjanjian perkawinan maka kemungkinan besar akan dibatalkan dan juga akan dikenakan sanksi.Kata kunci: perjanjian perkawinan, adat batak toba, hak Perempuan.